Critical Ecological Roles, Structural Attributes and Conservation of Old Growth Forest: Lessons From a Case Study of Australian Mountain Ash Forests - Lindenmayer, David; Bowd, Elle (Frontiers in Forests and Global Change, 2022)
Old growth is a critical growth stage in many forest types globally. It has many key ecological roles including biodiversity conservation, carbon storage and the provision of services such as water production. The extent of old growth forest has been declining in many ecosystems around the world, with major ecological and ecosystem service consequences. Important insights about such declines, as well as the structure, function and conservation of old growth forest, can be gained from detailed cross-sectional and longitudinal studies of different age cohorts within a given forest ecosystem. In this review article, we outline key insights into the characteristics of, and threats to old growth forests, using the Mountain Ash (Eucalyptus regnans) forests of the Central Highlands of Victoria, south-eastern Australia as a detailed case study. These forests are dominated by the tallest flowering plants on earth and have been subject to several decades of intense study. These studies show that old growth Mountain Ash forests are characterized by (among other features): giant trees (approaching 100 m tall and sometimes exceeding 20 m in circumference), numerous trees with hollows, an understorey of Acacia and rainforest trees, a range of plant and animal species that are rare or absent in younger aged stands, and moist, nutrient-rich soils. The area of old growth Mountain Ash forest has declined to 1.16% of the ∼141,000 ha area occupied by ash-type forests in the Central Highlands region. This is up to 60 times less than it was at the time of European colonization ∼220 years ago. The loss of old growth has major implications for bird, mammal and other biodiversity, as well as for carbon storage and water production for human consumption. The main drivers of old growth decline are recurrent wildfire, widespread clearcutting, and a logging-fire interaction in which cut and then regenerated forests become more flammable and are at significantly elevated risk of burning at high (stand replacing) severity. Climate change is also a driver of old growth decline both through elevating the mortality of large old living trees and underpinning an increase in the frequency of high severity wildfire. These interacting drivers mean that restoring old growth Mountain Ash forest will be an ecological and policy challenge. We argue that a first step must be to cease all commercial logging in the Mountain Ash ecosystem to allow new cohorts of old growth forest to be recruited and thereby expand the extent of the old growth estate. In addition, the Government of Victoria should revert to a past definition of old growth that made it easier for forest to qualify for protection. Given there are high risks of recurrent high-severity wildfire in the existing Mountain Ash forest estate which is dominated by highly flammable young regrowth forest, new technologies (such as the use of drones and satellites) are needed to rapidly detect and then suppress ignitions before fires become large and difficult to control. Mountain Ash forests have provided an important natural laboratory for understanding the dynamics, management and conservation of old growth forest. They have also helped generate some valuable general perspectives likely to be relevant to other forest ecosystems globally. These include: (1) the critical value of multi-facetted cross-sectional and longitudinal studies in quantifying attributes of, and threats to, old growth forest, (2) the need for a carefully crafted definition of old growth that will typically be ecosystem-specific and based on the time required to develop key ecosystem attributes (e.g., large old trees), (3) the importance of rigorous protection measures because poor decisions that result in the loss of old growth now will take prolonged periods to rectify, and (4) setting protection levels that are relative to the existing spatial coverage of remaining old growth and the extent and impacts of stressors driving old growth decline.